A Singular Nonlinear History-Dependent Cohesive Zone Model: Is it Possible?. Issue 3 (20th May 2020) - Argatov, I I
Summary: A history-dependent cohesive zone model is considered in the linear elasticity framework with the cohesive stresses governed by the fracture condition formulated in terms of a nonlinear Abel-type integral operator. A possibility for the cohesive stresses to possess a weak singularity has been examined by utilizing asymptotic modeling approach. It has been shown that the balance of the leading-term asymptotic representations in the model equations is possible for nonsingular cohesive stresses only.